A Comparative Study of Electrochemical, Spectroscopic and Structural Properties of Phenyl, Thienyl and Furyl Substituted Ethylenes. Issue 9 (28th March 2017) - Viglianti, Lucia; Villafiorita‐Monteleone, Francesca; Botta, Chiara; Mussini, Patrizia R.; Ortoleva, Emanuele; Cauteruccio, Silvia; Licandro, Emanuela; Baldoli, Clara
Abstract: a detailed electrochemical and photophysical comparative study of three parallel series of phenyl, thienyl and furyl substituted ethylenes has been carried out, implemented by the computational calculation of selected terms. Relationships have been highlighted between molecular structure (number and type of aromatic rings) and important functional properties (in particular, electronic features and oligomerization ability). Interestingly, some of the studied heteroaryl‐ethylenes show emission in the solid state displaying an aggregation‐induced emission behavior. Abstract : A detailed electrochemical and photophysical comparative study of three parallel series of phenyl, thienyl and furyl substituted ethylenes has been carried out, supported also by the computational study of selected terms. A palette of interpretative/predictive guidelines is thus made available concerning the redox and spectroscopic properties of (hetero)arylethylenes showing the relationship between molecular structure (number and type of aromatic rings) and important functional properties.